Incidence, risk factors and prevention of stoma site incisional hernias: a systematic review and meta‐analysis. (8th September 2018) - Lambrichts, D. P. V.; de Smet, G. H. J.; van der Bogt, R. D.; Kroese, L. F.; Menon, A. G.; Jeekel, J.; Kleinrensink, G‐J.; Lange, J. F.
Abstract: Aim: Stoma reversal might lead to a stoma site incisional hernia. Recently, prophylactic mesh reinforcement of the stoma site has gained increased attention, supporting the need for accurate data on the incidence of and risk factors for stoma site incisional hernia and to identify high‐risk patients. The aim of this study was to assess incidence, risk factors and prevention of stoma site incisional hernias. Method: Embase, MEDLINE, Web of Science, Cochrane and Google Scholar databases were searched. Studies reporting the incidence of stoma site incisional hernia after stoma reversal were included. Study quality was assessed with the Newcastle–Ottawa Scale and Cochrane risk of bias tool. Data on incidence, risk factors and prophylactic mesh reinforcement were extracted. Results: Of 1440 articles found, 33 studies comprising 4679 reversals were included. The overall incidence of incisional hernia was 6.5% [range 0%–38%, median follow‐up 27.5 (17.54–36) months]. Eleven studies assessed stoma site incisional hernia as the primary end‐point, showing an incidence of 17.7% [range 1.7%–36.1%, median follow‐up 28 (15.25–51.70) months]. Body mass index, diabetes and surgery for malignant disease were found to be independent risk factors, as derived from eight studies. Two retrospective comparative cohort studies showed significantly lower rates of stoma site incisional hernia with prophylactic mesh reinforcement compared with nonmesh controls [6.4% vs 36.1% ( P = 0.001); 3% vs 19% ( P = 0.04)]. Conclusion: Stoma site incisional hernia should not be underestimated as a long‐term problem. Body mass index, diabetes and malignancy seem to be potential risk factors. Currently, limited data are available on the outcomes of prophylactic mesh reinforcement to prevent stoma site incisional hernia.